Endovascular thrombectomy is cost-effective in acute basilar artery occlusion stroke - Schwarting, Julian; Rühling, Sebastian; Bodden, Jannis; Schwarting, Stéphanie K.; Zimmer, Claus; Mehrens, Dirk; Kirschke, Jan S.; Kunz, Wolfgang G.; Boeckh-Behrens, Tobias; Froelich, Matthias F. (Frontiers in neurology, 2023)
Objective: Endovascular thrombectomy is a long-established therapy for acute basilar artery occlusion (aBAO). Unlike for anterior circulation stroke, cost-effectiveness of endovascular treatment has not been evaluated and is urgently needed to calculate expected health benefits and financial rewards. The aim of this study was therefore to simulate patient-level costs, analyze the economic potential of endovascular thrombectomy in patients with acute basilar artery occlusion (aBAO), and identify major determinants of cost-effectiveness. Methods: A Markov model was developed to compare outcome and cost parameters between patients treated by endovascular thrombectomy and patients treated by best medical care, based on four recent prospective clinical trials (ATTENTION, BAOCHE, BASICS, and BEST). Treatment outcomes were derived from the most recent literature. Uncertainty was addressed by deterministic and probabilistic sensitivity analyses. Willingness to pay per QALY thresholds were set at 1x gross domestic product per capita, as recommended by the World Health Organization. Results: Endovascular treatment of acute aBAO stroke yielded an incremental gain of 1.71 quality-adjusted life-years per procedure with an incremental cost-effectiveness ratio of $ 7,596 per QALY. This was substantially lower than the Willingness to pay of $ 63,593 per QALY. Lifetime costs were most sensitive to costs of the endovascular procedure. Conclusion: Endovascular treatment is cost-effective in patients with aBAO stroke.
Gesehen am 20.06.2023